SIALOLITHIASIS OF LOWER LIP - HISTOPATHOLOGICAL INTERPRETATION - Bajpai, Manas; Pardhe, Nilesh (Journal of Ayub Medical College Abbottabad, 2017)
A 38 year old male presented to the Department of Oral and Maxillofacial Pathology for the evaluation of a swelling of the lower lip from 2 years. Initially it was asymptomatic, but few days back the lesion was bitten by the patient accidentally during normal mastication, resulted in a mild pain. Intra oral examination revealed a 2 Ã— 2 cm, firm, movable, well defined, nodular swelling. The color of the overlying mucosa was red and a rough keratotic papillary surface was noted at one place